PEMETAAN PEMETAAN DAN PENETAPAN BATAS WILAYAH SECARA PARTISIPATIF PASCA PEMEKARAN DI NAGARI KAMANG MUDIAK DAN NAGARI PERSIAPAN KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Muhammad Arifin; Endah Purwaningsih (JURNAL BUANA, 2021)
The purpose of this study is to know: (1) Steps and processes in mapping the nagari boundaries of Nagari Kamang Mudiak and Prepared Nagari (2) Making the Administrative Map of Nagari Kamang Mudiak and Prepared Nagari. The type of research is descriptive with a qualitative approach. This study uses qualitative methods, cartometrics and Focus Group Discussion (FGD) to obtain the information about the nagari boundaries of Nagari Kamang Mudiak and Prepared Nagari and involves community participation in the process of determining the Nagari Boundaries of Nagari Kamang Mudiak and Prepared Nagari. The results obtained from this research are steps and processes of mapping the Nagari Boundaries of Nagari Kamang Mudiak and Prepared Nagari divided into 3 processes and stages, namely a. collecting information, data and documents, b. tracking and data retrieval of nagari boundaries and, c. processing data from the survey results of nagari boundaries. From the 3 processes and stages obtained results in the form of Administration Map of Nagari Kamang Mudiak and Prepared Nagari.